Peran Pendidikan Sebagai Pondasi Utama dalam Menyikapi Dekadensi Moral pada Generasi Z - Fadia Puja Ainun; Heni Setya Mawarni; Nida Nimatul Fauzah; Reza Mauldy Raharja (Universitas 45 Surabaya, 2024)
The progress of the times which allows developments in science and technology to provide very significant new patterns in the implementation of human life. Where humans can access various desired information in a very short time, communicate with other individuals without being limited by distance and time. Humans have now entered an era of generational change, from the millennial generation to the z generation. Where Generation Z is a generation whose development is in line with the growth of technology, which has caused this generation to become accustomed to openness of information and adapt to the values ​​brought by this openness. This causes this generation to experience moral decadence, because of the shift in values ​​that occurs within humans. The research method used in this research is a literature review, where researchers use various existing data and utilize various references in the form of information from articles, journals, books and various other literature whose validity and validity can be confirmed. The results of this research state that education is one solution for dealing with moral decadence among teenagers. The family also plays a very important role in overcoming problems that occur. Through ideal and sufficient education, problems, especially moral decadence, can be overcome or even disappear.